2022
DOI: 10.1080/17482631.2022.2122138
|View full text |Cite
|
Sign up to set email alerts
|

The influencing factors of clinical nurses’ problem solving dilemma: a qualitative study

Abstract: Purpose Problem solving has been defined as “a goal-directed sequence of cognitive and affective operations as well as behavioural responses to adapting to internal or external demands or challenges. Studies have shown that some nurses lack rational thinking and decision-making ability to identify patients’ health problems and make clinical judgements, and have poor cognition and response to some clinical problems, easy to fall into problem-solving dilemma. This study aimed to understand the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Unlike previous studies, our study included only new graduate nurses in the 22-29-year age range, who had worked less than a year and were still in transition. Previous studies have reported that the age of senior nursing students is negatively correlated with their learning outcomes; confdence in managing multiple patients [49] and nursing skill competency [46] decrease as age increases. Considering that confdence and competence on the learning curve are likely to grow with experience [50], we cannot confrm the efect of age on the retention of nurses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike previous studies, our study included only new graduate nurses in the 22-29-year age range, who had worked less than a year and were still in transition. Previous studies have reported that the age of senior nursing students is negatively correlated with their learning outcomes; confdence in managing multiple patients [49] and nursing skill competency [46] decrease as age increases. Considering that confdence and competence on the learning curve are likely to grow with experience [50], we cannot confrm the efect of age on the retention of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting fnding is that the participants who had confdence in clinical problem-solving when they were nursing students tended to remain in their jobs as new nurses. Problem-solving skills are a core competency of professional nurses, who need to continuously identify patients' health problems and make clinical judgments in patient care [45,46]. Nurse educators should pay attention to the problem-solving ability of new graduate nurses during the transition, optimize the new nurse orientation program, and conduct a series of training sessions using situational simulation and new media technology to improve their clinical reasoning [46].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with a Chinese study that showed that research-oriented cultures encourage continuous learning and enhance analytical and critical thinking abilities in newly graduated Chinese nurses [ 18 ]. In a separate study conducted in China, clinical nurses who can adapt to the changes brought about by research are more likely to make practical problems solving efforts [ 19 ]. Research-friendly workplace environments are frequently associated with greater job satisfaction, according to a study of nursing faculty members working in Canadian colleges and universities [ 20 ].…”
Section: Discussionmentioning
confidence: 99%